Wire Crossing Time Correlate with Left Ventricular End-Diastolic Pressure in Patients with ST Segment Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention - Indra Widya Nugraha; Anggoro Budi Hartopo; Nahar Taufiq (The Indonesian Heart Association, 2020)
Backgrounds: Mortality and morbidity in acute myocardial infarction depend on the extent of the infarct area. Rapid recovery of coronary artery blood flow with primary percutaneous coronary intervention (pPCI) can limit the extent of infarction and improve left ventricular function. Acute myocardial infarction reduce diastolic function, which in the early stage of diastolic dysfunction, there is an increase in left ventricular end-diastolic pressure (LVEDP). The non-invasive marker of E/e’ ratio is an accurate parameter of increased LVEDP.Methods: This was a cross-sectional study enrolled consecutive patients with ST Segment Elevation Myocardial Infarction (STEMI) who underwent pPCI at Dr. Sardjito Hospital. The wire crossing time was calculated from the onset of chest pain until the guidewire crossed the infarct-related artery during the pPCI procedure. The E/e’ ratio was determined by transthoracic echocardiography which performed within 48 hours after the primary PCI. Correlation between the wire crossing time and the E/e’ ratio was assessed by the Pearson correlation test. The value of p <0.05 was considered statistically significant.Results: A total of 40 patients were enrolled in this study. The mean wire crossing time was 12.73±5.22 hours. The median value of the E/e’ ratio was 8.36 (range: 4.71-22.00). There was a moderate strength and significant correlation between the wire crossing time and the E/e’ ratio (r = 0.572; p <0.001). Patients with E/e’ ratio >15 had significantly longer wire crossing time than in patient with E/e’ ratio ≤15 (20.21±2.5 hours vs. 11.41±4.39 hours; p <0.001; respectively). The wire crossing time was independently associated the E/e’ ratio (r = 0.463; p = 0.003).Conclusion: There was a moderate strength and significant positive correlation between the wire crossing time and increased LVEDP, an earlier marker of diastolic dysfunction, measured by E/e’ ratio using TTE in patients with STEMI underwent pPCI.